The Effectiveness of Project-Based Blended Learning Models in Cryptography Courses (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of science and technology requires universities not only tomatter but also to have abilities in their respective fields including computernetworks. The unavailability of network design laboratory and its minimum,network design, computer network design and flexibility of face-to-face timein the discussion of material compiled not in accordance with thecompetencies in this course. To overcome these deficiencies in learningactivities, development of a project-based blended learning model is carriedout.The development carried out in this study uses the Puslitjaknovdevelopment model which reduces the Borg and Gall stages to five stagesnamely product analysis, initial product design, expert validation andrevision, field trials and implementation. The subjects of this study werestudents of STMIK Indonesia Padang who took the Computer NetworkDesign and Management course in the 2019 academic year. Data werecollected by interview, observation, questionnaire and test. Data wereanalyzed using quantitative and qualitative methods to produce researchproducts in the form of books, modules, learning plans and manuals for theuse of learning applications. Product validation by experts, practicality testscarried out by users and effectiveness tests with student learningoutcomes.Based on the results of data analysis, the results of this study are:1) Research has successfully developed a project-based blended learningmodel in computer network design and management courses. 2) Thedeveloped learning model syntax consists of 9 stages / syntax. 3) Insupporting learning activities, modules, RPS and manuals are used forlearning applications. All products and models developed have beendeveloped and are categorized as valid, practical and effective.